KKN-PPM LITERASI DESA DI DESA NGEGEDHAWE KECAMATAN AESESA KABUPATEN NAGEKEO - Agustinus F. Paskalino Dadi; Virgilius Bate Lina; Maria Helena Carolinda Dua Mea (Jurnal Aplikasi dan Inovasi Iptek, 2020)
The Village Literacy KKN-PPM Program was held on 27th July to 7th September 2019. This program was led by a team consists of three lecturers, 20 students and partnering Ngegedhawe Villager. This program emerged as an awareness of the team towards the reality of the lives of residents in Ngegedhawe Village in terms of literacy. Based on observations and interviews it was found that the Ngegedhawe people are lack in reading and writing, and in cultural-citizenship literacy. Citizens do not have adequate access to information in the form of a place to read and increasingly decline the nationality and cultural character of the citizens (especially children and young people) as a result of modernization and globalization. On that basis, the KKN-PPM takes the theme of Village Literacy which is carried out with several methods in the form of the construction of reading house, the provision of reading material, counseling or socialization of literacy and cultural-citizenship literacy, cultural performances and competitions. Based on observations and interviews with several randomly selected villagers, it was found that the Village Literacy KKN-PPM program had a very positive influence on Ngegedhawe villagers where there was an increase in knowledge and awareness in literacy and literacy of citizenship, as well as the availability of a reading house and reading material that can support the improvement of the literacy skills of citizens in the subsequent times.